2021
DOI: 10.1002/aenm.202102865
|View full text |Cite
|
Sign up to set email alerts
|

Gradient‐Structuring Manipulation in Ni3S2 Layer Boosts Solar Hydrogen Production of Si Photocathode in Alkaline Media

Abstract: consists of a photocathode and photoanode to drive the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), separately. [5] To fulfill a practical PEC device, the photocathode needs to be placed in the same electrolyte as the photoanode. [6] It has long been known that HER is more favorable in acid than in alkaline solutions when taking the benchmark platinum-based catalysts as an example, due to the lower activation energy of the water dissociation step involved in acid HER. [7,8] Neverthele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 74 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…In the field of photocatalytic hydrogen production, one of the core problems that experts have been focusing on is how to improve the separation efficiency of photogenerated carriers. [ 39 ] However, we know that the reasonable design of the buffer layer can have a useful effect on charge separation. It is particularly important to evaluate the charge separation ability before hydrogen production experiments of photocathode Pt‐TiO 2 /In x Cd 1− x S/Cu 3 BiS 3 under sunlight.…”
Section: Resultsmentioning
confidence: 99%
“…In the field of photocatalytic hydrogen production, one of the core problems that experts have been focusing on is how to improve the separation efficiency of photogenerated carriers. [ 39 ] However, we know that the reasonable design of the buffer layer can have a useful effect on charge separation. It is particularly important to evaluate the charge separation ability before hydrogen production experiments of photocathode Pt‐TiO 2 /In x Cd 1− x S/Cu 3 BiS 3 under sunlight.…”
Section: Resultsmentioning
confidence: 99%
“…[15] Ni 3 S 2 /NiO x -15 having the largest double-layer capacitance (C dl = 72.2 mF cm −2 ) also indicated that it had the most exposed catalytically active sites (Figure S30, Supporting Information). [16] The selectivity for HMFOR over the OER is another important issue because the latter is the predominant potential side reaction in alkaline electrolytes. The potential demand at the same current density was significantly reduced after adding 20 mm HMF to 1 m KOH (ΔE = 295 mV at j = 100 mA cm −2 ) (Figure S31, Supporting Information), implying that HMFOR on Ni 3 S 2 /NiO x -15 was more favorable than the OER.…”
Section: Electrochemical Hmf Oxidation Performancementioning
confidence: 99%
“…A gradient-structured Ni 3 S 2 (G-Ni 3 S x O 2−x ) layer was added via a thermoelectrodeposition method, which acts as a passivation layer as well as the PEC-HER catalyst coated over p-Si [Fig. 7e] 72 . In a 1 M NaOH aqueous solution, G-Ni 3 S x O 2-x /p-Si demonstrated extraordinary PEC performance, with a noteworthy onset potential (E op = 0.39 V RHE ) and a photocurrent density of −33.8 mA cm −2 at…”
Section: Ni-based Her Catalystsmentioning
confidence: 99%